Three-by-three basketball: Inertial movement and physiological demands during elite games - Montgomery, P. G.; Maloney, B. D. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To determine the demands of elite male and female 3×3 basketball games and compare these between various competition levels. Methods: A total of 361 males and 208 females competing in the Under-18 World, Senior European, and World Championships and selected professional tournaments had game demands assessed by wearable technology (global positioning system, inertial measurement, heart rate) along with postgame blood lactate and perceived responses. Differences in the means were compared using magnitude-based inferences and reported with effect size and 90% confidence limits, along with the percentage difference (effect size; ±90% confidence limits, %) of log-transformed data. Results: PlayerLoad™ and PlayerLoad/mi during play was 127.5 (31.1) and 6.7 (1.5) for males and 128.5 (32.0) and 6.5 (1.4) for females, respectively, with small differences between junior, senior, and professional levels. There were small differences in accelerations >3.5 m/s between competition levels up to 0.31; ±0.20, 6.9% for males and 0.29; ±0.19, 10.8% for females and for decelerations >3.5 m/s, 0.29; ±0.19, 15.6% for males and 0.26; ±0.19, 5.4% for females, with European Championships generally greater than other levels. Average game heart rate was 165 (18) and 164 (12) beats·min-1 for males and females, with no difference between levels. Average rating of perceived exertion was 5.7 (2.1) and 5.4 (2.0) for males and females. Conclusions: 3×3 basketball games require high-speed inertial movements within limited distance, creating a relatively high physiological response. Practitioners working with 3×3 players should endeavor to focus on the attributes that will improve these player characteristics for greater success.